2004
DOI: 10.1097/01.ccm.0000105309.27519.27
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine infusion for the management of persistent pulmonary hypertension of the newborn*

Abstract: The use of adenosine infusion in combination with inhaled nitric oxide may be a potentially valuable therapeutic option for the treatment of pulmonary hypertension of the newborn. Neonates with irreversible lung pathology may not respond to adenosine infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…However, the improvement in oxygenation was not sustained, and some infants had a decrease in oxygenation presumably related to worsening of VQ mismatch due to an increase in total pulmonary flow. Ng et al [106] reported that adenosine infusion (50 mg/kg/min) improved oxygenation and decreased pulmonary artery pressure in six of nine infants with PPHN already receiving INO therapy. ATPMgCl 2 infusion was shown to cause selective pulmonary vasodilation in children with post-operative pulmonary hypertension [107].…”
Section: Adenosine and Atpmentioning
confidence: 98%
“…However, the improvement in oxygenation was not sustained, and some infants had a decrease in oxygenation presumably related to worsening of VQ mismatch due to an increase in total pulmonary flow. Ng et al [106] reported that adenosine infusion (50 mg/kg/min) improved oxygenation and decreased pulmonary artery pressure in six of nine infants with PPHN already receiving INO therapy. ATPMgCl 2 infusion was shown to cause selective pulmonary vasodilation in children with post-operative pulmonary hypertension [107].…”
Section: Adenosine and Atpmentioning
confidence: 98%
“…Posteriormente, Ng et al (29) demonstraram que a associação de dopamina, adenosina e óxido nítrico determina um aumento na oxigenação, com manutenção adequada de pressão arterial sistêmica.…”
Section: Discussionunclassified
“…His weight being too low, the possibility of extracorporeal membrane oxygenation assistance was ruled out. We therefore started an infusion of adenosine at 50 g/kg/min as recommended by Konduri et al (1) and by Ng et al (2), once approval of our Institutional Review Board and the parents was obtained.…”
Section: Case Descriptionmentioning
confidence: 99%